Wearable Electronics: High‐Resolution Patterning and Transferring of Graphene‐Based Nanomaterials onto Tape toward Roll‐to‐Roll Production of Tape‐Based Wearable Sensors (Adv. Mater. Technol. 12/2017). Issue 12 (12th December 2017) - Oren, Seval; Ceylan, Halil; Schnable, Patrick S.; Dong, Liang
Abstract : In article number1700223, Liang Dong and co‐workers present a graphene patterning and transferring method to manufacture low‐cost, installation‐free, wearable electronic sensors on adhesive tapes. The minimum feature size of the transferred graphene patterns is in the order of a few micrometers. Smart gloves are demonstrated to monitor human body motion. Wearable leaf sensors are realized to monitor plant transpiration process and water status.